Dampak Merger Terhadap Aset Kepemilikan Kapal Pt. Pelabuhan Indonesia (Persero) - Ruth Elizabeth Marlamb Putri; Lewiandy Lewiandy (LPPM Universitas Ekasakti Padang, 2023)
Mergers are one way to maintain a company, which in this case has strategic efficiency in the survival of a company. When running a business, you definitely have many competitors, therefore you need a structure that can save a company. Regarding this corporate action, it was also carried out by the State-Owned Enterprise, namely Pelindo. Pelindo carried out this merger action in order to improve maritime connectivity throughout Indonesia and increase competitiveness within the State-Owned Enterprise. After the merger, all property/assets and responsibilities will be transferred to the company that can be established, therefore this journal will discuss the above matters further.